Digital Marketing in Industrial Revolution 4.0 - Soegoto, Eddy Soeryanto; Raihan, Naufal (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to build the brand awareness around millennial people. This research used descriptive method to see the role of digital marketing and the brand awareness in fashion industry. In this era, digital of marketing is a strategy to increase consumer awareness for fashion brand, especially a boy fashion. As there are lot of internet user, it can increase brand awareness in a product at this digital era.